Ekolinguistik Kebambuan Dalam Masyarakat Bahasa Batak Toba - Tomson Sibarani (Balai Bahasa Sumatera Utara, 2019)
Ekolinguistik, an interdisciplinary studies see a link between ecology (ecosystem), and linguistics (linguistics). In his discussion, and interdisciplinary nature, this study involves other studies, including, sociology, anthropology, psychology, and political science. Aspects of social-ecological greatly affects ,cared, balance, and ,haritage environment for future generations. Wisdom-local ecological knowledge should be followed-discourse to include in a healthy environment and green (greenspeak), in view of the soul (concepts ideological, philosophical, socio-ecological) character local communities in the local wisdom. Changes can be caused by the emergence of new tools are more practical needs, but do not think of nature and can cause damage to the environment such as the appearance of materials that are made of plastic, atom, iron and aluminum. This can damage the environment and can also damage the language vocabulary is the loss of the name Toba Batak previous tool because it is not used. So from the diversity of languages that are changing the ecology in a few words will be no longer used by the public so that the successor of native speakers of the language, they will feel strange when hearing diversity of languages was once used in his own language. Lifestyle changes Toba Batak society has changed so much and not enough nature as provider and life. Social patterns are also changing from mutual cooperation leads are individuals. Ecology is closely related with the language because every flora and fauna of wealth has become a name that speaking people.